THE ANALYSIS OF THE WORKLOAD OF INPATIENT MEDICAL RECORD DATA UPDATE STAFF USING WORKLOAD INDICATOR OF STAFFING NEED METHOD TO SUPPORT WORK EFFECTIVENESS IN HOSPITAL IN BANDUNG - M Dana Prihadi; Pri Agung Danarahmanto; Julia Famor Pratami (Journal of Business Studies and Management Review, 2021)
Workload analysis is a human resource planning activity that aims to determine manpower needs in the organization. It means that the number of employees have to be adjusted to the existing workload, so that the employees’ work effectiveness can be implemented properly. The population were inpatient medical record data update staff, by using quote sampling technique from the workload of five (5) staffs of inpatient medical record data update. The type of research was descriptive with quantitative approach. The aims of the research were to discover the job descriptions of inpatient medical record data update, to find out the need of human resource in inpatient medical record data update, and to know the work effectiveness of inpatient medical record data update. The data were collected by using interview and documentation techniques. The results of the research were the number of data update files completed in 2019 amounted to 40,910 files out of 43,764 files, with five (5) staffs available. Based on the results of the research on human resource planning in inpatient medical record data update section using Work Indicator of Staffing Need (WISN) method, the result of calculation using the WISN method was 6.24 or 6 in decimal. Based on the calculation, it is advised that the hospital needs to consider adding one more staff in medical record data update section, so that the work effectiveness of the staff can be implemented properly.